Business Incubators - DJERRI, Roukia; KAMEL, Nadia (Journal of Human Sciences, 2025)
Within the context of the rapid economic and technological advances being witnessed by the world’s nations and the encouragement of young people, especially in developing countries, among which graduates of universities and educational institutions who aspire to enter the world of finance and business, it emerged a very important mechanism that contributes to achieving this, namely, startups, which help reviving and developing The local economy, and also promoting the social situation and eliminating a significant part of the unemployment rate as well, however, startups, for their survival, are constantly looking for guidance and support from more knowledgeable and experienced parties. Furthermore, they seek to reach a position that allows them achieve continuity and growth, as we know These institutions lack experience and skills in most cases, in addition to the weaknesses in their financial resources that would allow them to survive، In order to ensure the continuity and growth of startups and keep pace with the world of competition and competitiveness, It emerged a mechanism that provides support to them, represented in business incubators as entities which provide all forms of support beginning with the initial study of the project idea , through investment, industry and marketing processes, together with marketing and export services.